Muslim women in the economy: development, faith and globalisation - Samani, Shamim; Marinova, Dora (Routledge research in religion and development, 2020)
Cover -- Half Title -- Series Page -- Title Page -- Copyright Page -- Table of Contents -- List of illustrations -- Acknowledgments -- List of contributors -- Introduction: Changing prospects for Muslim women in the global economy -- PART 1: Gender policies and economic participation -- 1. Progressing in a man's world: Women's workforce participation in Bangladesh -- 2. Gender parity through the Saudi Vision 2030: Female representation in English as a Foreign Language textbooks -- 3. Cultural assimilation policies in Bulgaria and the plight of Muslim women